Developing a neuropsychological measurement to capture workplace learning. (8th August 2016) - Lagrosen, Yvonne; Travis, Frederick
Abstract : Purpose: The purpose of the paper is to examine variables to be included in a measurement instrument which measures workplace learning related to recent research into quality management and brain functioning. Design/methodology/approach: A literature review was conducted, investigating measures of workplace learning as well as the connections between brain functioning and management. Further studies will use the brain integration scale to compare levels of brain integration with measures of workplace learning. Findings: The variables "empathy", "presence and communication", "continuity", "influence", "development", "work-integrated learning" and "flow" were found to be relevant from the literature review to be tested for inclusion in the measurement instrument. A measurement model with these variables included has been developed. Research limitations/implications: This paper is conceptual in its nature. Empirical studies are needed to validate the propositions. Practical implications: The proposed measurement instrument can be used by managers to gain insight into underlying mechanisms in the organizational culture that influence employees' learning and potential for development. Thus, it can aid managers to achieve profound learning in their organizations, which is necessary for continuously maintaining high quality of products and services. Social implications: For society, the implementation of the proposed measurement instrument in companies could lead to better health and higher job satisfaction among employees. Originality/value: Traditional ways of measuring working environment are rarely connected to brain functioning of the employees. Only requiring small resources, this approach adds to an understanding of underlying mechanisms.